Increase Elementary School Students' Interest in Learning During Covid-19 with Teaching Materials Using E-Books - Benjamin Brunel; Jayshree Martin; Wang Fang (Lingeduca: Journal of Language and Education Studies, 2023)
The purpose of this research is to increase students' interest in learning in elementary schools during Covid-19 with e-book teaching materials by utilizing technology in learning media, especially using digital books (e-books) through computer intermediaries, laptops or smartphones. Since the existence of Covid-19, the level of interest in learning from students has been very minimal, because educators are less creative in using technology when carrying out the learning process, so that students are less interested in doing learning, by utilizing technology published in digital form can be used by students to facilitate students in learning and increase student interest in learning during the Covid-19 pandemic by displaying information in the form of text, images, audio, video, animation, narration, music, and other multimedia. The method used in this study is a quantitative research method, in which this method researchers can collect data by means of in-depth interviews using the Google form. Because of that, with the e-book media, researchers hope that students' interest in learning can increase even though learning is still done online